A Bibliometric Analysis of Ecotourism Development for Sustainable Tourism - Haryanto, Eko; Makiya, Kiki Rizki; Noviati, Fitria (International Journal Of Tourism, 2024)
Sustainable tourism development is a widely applied concept in various regions, both in Indonesia and abroad. Ecotourism, in particular, is a form of tourism activity that ensures the implementation of sustainable tourism. The theme of ecotourism has been extensively researched in various countries. Ecotourism has become a significant research theme over the last two decades, yielding critical results on environmental and natural conditions.Purpose: This study aims to examine research in the field of ecotourism and sustainable tourism from 2018 to 2023.Research methods: Using Publish or Perish (PoP) software to gather data from the Google Scholar database, specifically focusing on journal articles with the keywords "ecotourism" AND "sustainable tourism." A total of 500 journal articles were collected and the data in the Research Information System (RIS) format. I then entered this data into the Mendeley References application and processed the tabulated data using Microsoft Excel. The data was further analyzed using VosViewer software to map research topics and interpret their relationships and relevance values.Results and discussions: The results of the analysis show that research with the theme of ecotourism has indeed been widely carried out and has a close relationship with similar research themes as following existing research clusters.Conclusion: Specific themes such as marine ecotourism, ecotourism management, local communities, ecotourism projects, sustainable development, relationships, and sustainable tourism are likely to be important research areas in the future. It's worth noting that the journal articles obtained from the Google Scholar database may include articles from both accredited and non-accredited journals. For future research, it would be beneficial to use more credible databases such as Web of Science or Scopus to ensure that the articles collected are widely reviewed and credible, as they are published in reputable journals